Crystal structure of the kinesin motor domain reveals a structural similarity to myosin - Kull, F. Jon (1996)
Kinesin is the founding member of a superfamily of microtubule-based motor proteins that perform force-generating tasks such as organelle transport and chromosome segregation1,2. It has two identical ~960-amino-acid chains containing an amino-terminal globular motor domain, a central α-helical region that enables dimer formation through a coiled-coil, and a carboxy-terminal tail domain that binds light chains and possibly an organelle receptor1. The kinesin motor domain of ~340 amino acids, which can produce movement in vitro3, is much smaller than that of myosin (~850 amino acids) and dynein (1,000 amino acids), and is the smallest known molecular motor. Here, we report the crystal structure of the human kinesin motor domain with bound ADP determined to 1.8-Å resolution by X-ray crystallography. The motor consists primarily of a single α/β arrowhead-shaped domain with dimensions of 70 × 45 × 45 Å. Unexpectedly, it has a striking structural similarity to the core of the catalytic domain of the actin-based motor myosin. Although kinesin and myosin have virtually no amino-acid sequence identity, and exhibit distinct enzymatic4–6 and motile7–10 properties, our results suggest that these two classes of mechanochemical enzymes evolved from a common ancestor and share a similar force-generating strategy.